It Takes a (Virtual) Village: Exploring the role of a career community to support sensemaking as a proactive socialization practice - Good, Darren; Cavanagh, Kevin (Frontiers in Psychology, 2017)
Scholars have long advocated for individuals to play a more proactive role during organizational entry rather than relying on institutionally led processes. The primary benefit being that the newcomer moves from passive recipient, dependent on the institution to highlight relevant information, to active agent with self-determined sources and methods to aid in adjustment. A virtual career community made up of 12 first year business faculty members was created to provide such a self-determined source of support during the transition from doctoral studies to full-time assistant professorship. After the entry period (1 academic year), the interactions in this community were used as data for a phenomenon driven research study. The results illustrate how a virtual career community could be used as a proactive socialization tool by encouraging sensemaking amongst first year faculty peers. The sensemaking process consists of perceived contrasts and tensions, followed by positive and negative self-disclosures, community feedback and the experience of cognitive-behavioral shifts. The findings also expand the proactive use of external referents during organizational entry, which previously had only looked at friends and family members of the newcomer. Keywords: career communities, sense-making, organizational entry, proactive socialization, growth, development